376 From Core to Margin: Intratumoral Differences in Cancer Hallmarks Depend on Spatial Localization of Cells in Glioblastoma. (April 2023) - Suarez-Meade, Paola; Figueredo, Luisa F.; Roberts, Mckinley; Brooks, Mieu; Zarco, Natanael; Guerrero-Cazares, Hugo; Chaichana, Kaisorn L.; Schiapparelli, Paula; Quinones-Hinojosa, Alfredo
Abstract : INTRODUCTION: Glioblastoma (GBM) carries a dismal prognosis due to its invasive nature. Studies show that GBMs have transcriptionally heterogeneous cell populations within the same tumor. However, information regarding the biological behavior of different intratumoral populations has never been demonstrated in vitro. METHODS: GBM patients who underwent resective surgery were consented for research. MRI-guided images were registered during resection to localize the area where samples were obtained. Two GBM cell lines were established from the same patient for each case: margin and core cell line. Proliferation, migration, and stemness experiments were performed in vitro and intracranial implantation of tumors was then carried out to evaluate tumor behavior in vivo. RESULTS: 10 cell lines from 5 patients were established from the margin and the core. There were no differences in cell proliferation. Sphere area and limiting dilution assay (p < 0.01) show that cells derived from the margin have greater stemness capabilities. Cells from the margin have higher migratory abilities in transwell migration assay (p < 0.01 in 4/5 patients) and in real-time cell invasion monitoring (p < 0.01). Trend which was later noted in sphere invasion assay. In vivo studies demonstrate that both cell populations were capable of tumor engraftment with no differences in tumor growth by bioluminescence (p > 0.05). Nonetheless, tumors from the marginal area demonstrated a more diffuse phenotype and greater extension when compared core-derived tumors on histopathology . CONCLUSIONS: There is a large degree of behavioral heterogeneity between cells from the tumor core versus the margin. GBM cells from the margin have higher migration and stemness properties when compared to their core counterparts in vitro; suggesting that peripheral cells carry more aggressive phenotypes that could be responsible for treatment resistance and tumor recurrence